PROTECTION OF CONFIDENTIAL COMMUNICATION BETWEEN LAWYERS AND CLIENTS IN THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Đukić, Dimitrije (Glasnik Advokatske komore Vojvodine, 2020)
Confidentiality of communication is a very important human right that becomes even more important when communication is made between a lawyer and a client. Namely, for a lawyer to be able to adequately represent his client, the client must be sure that the information he/she entrusts to the lawyer will not reach third parties, ie that the communication will remain confidential. In this sense, protecting the confidentiality of communication between a lawyer and a client is very important not only for representing the client in each case but also for the proper functioning of the legal system. This paper aims to establish which articles of the European Convention protect the right to a confidential communication between a lawyer and a client and how this communication is protected in practice by the European Court of Human Rights. Also, the paper considers whether it is possible to prescribe a measure by which such an important right as the right to a privileged and confidential communication between a lawyer and a client could be limited and if so under what conditions.